Light-absorbing anisotropic film, method for producing same, laminate, and image display device

By forming an optimized dichroic substance arrangement structure and adjusting surface characteristics in the light absorption anisotropic film, the problem of poor black contrast in organic EL display devices is solved, and higher black contrast and tone stability are achieved.

CN119923582APending Publication Date: 2025-05-02FUJIFILM CORP
View PDF 67 Cites 0 Cited by

Patent Information

Application Number
CN202380062203.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-03
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art is difficult to achieve excellent black contrast when used in organic EL display devices, especially when black image display, and tone shifts are difficult to suppress.

Method used

By forming an arrangement structure based on dichromatic substances in the light absorption anisotropic film and reducing the size of the arrangement structure near the surface of the film, the specific implementation method includes adding a surfactant and a high molecular weight biased existence substance to the film, observing the cross section by scanning a transmission electron microscope, and adjusting the long axis length of the arrangement structure to meet specific average conditions.

Benefits of technology

The performance of black contrast in organic EL display devices is significantly improved, scattering during external light incident is reduced, and the orientation and durability of the film are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923582A_ABST
    Figure CN119923582A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a light-absorbing anisotropic film which exhibits excellent black contrast when used in an image display device; a method for producing the light-absorbing anisotropic film; and a laminate and an image display device which have the light-absorbing anisotropic film. This light-absorbing anisotropic film contains a dichroic material and a liquid crystal compound, and is characterized in that at least a portion of the dichroic material forms an array structure, and in a cross-section observed by a scanning transmission electron microscope, the liquid crystal compound has a refractive index of at least 90%. When the average value of the length of the long axis of the array structure observed in a region A up to 150 nm in the film thickness direction from the one surface is Ltop and the average value of the length of the long axis of the array structure observed in a region B up to 150 nm in the film thickness direction from the other surface is Llow, Lp is the average value of the length of the long axis of the array structure observed in the region B up to 150 nm in the film thickness direction, and Llow is the average value of the length of the long axis of the array structure observed in the region B up to 150 nm in the film thickness direction. The light-absorbing anisotropic film satisfies at least one of formula (1-1) and formula (1-2). Ltop is less than or equal to 35nm (1-1), and Llow is less than or equal to 35nm (1-2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light absorption anisotropic film and a method for manufacturing the same, a laminate and an image display device. Background Art

[0002] Light absorption anisotropic films are used in a wide variety of applications. For example, organic electroluminescent (EL) display devices have a structure using metal electrodes, so sometimes they reflect external light, causing contrast reduction and reflection problems. Therefore, in order to suppress the adverse effects caused by external light reflection, polarizing plates with light absorption anisotropic films have been used.

[0003] For example, Patent Document 1 discloses a polarizing plate having a polarizing layer (light absorption anisotropic film) formed of a composition containing a dichroic dye (dichroic substance) and a liquid crystal compound.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-023153 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] On the other hand, in recent years, in order to further improve the image quality, organic EL display devices are required to have excellent black contrast in the front direction. In addition, "excellent black contrast" means that when the image display device displays black, the color shift of black is suppressed.

[0009] Under such circumstances, the present inventors produced an organic EL display device having the polarizing plate described in Patent Document 1 and evaluated its black contrast. As a result, they found that it does not necessarily meet the standards required today.

[0010] Therefore, in view of the above circumstances, an object of the present invention is to provide a light absorption anisotropic film that exhibits excellent black contrast when used in an image display device, a method for producing the same, and a laminate and an image display device having the light absorption anisotropic film.

[0011] Means for solving technical problems

[0012] The present inventors have conducted intensive studies on the above-mentioned problems and have found that black contrast is improved by forming an array structure based on a dichroic substance in a film and reducing the size of the array structure near the surface of the film, thereby completing the present invention.

[0013] That is, the present inventors have found that the above-mentioned problems can be solved by the following configuration.

[0014] (1) A light absorption anisotropic film comprising a dichroic substance and a liquid crystal compound, wherein:

[0015] At least a portion of the dichroic material forms an array structure,

[0016] In a cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in region A from one surface to 150 nm in the film thickness direction is set to Ltop and the average value of the length of the major axis of the arrangement structure observed in region B from another surface to 150 nm in the film thickness direction is set to Llow, the above-mentioned light absorption anisotropic film satisfies at least one of the following formulas (1-1) and (1-2).

[0017] Ltop≤35nm (1-1)

[0018] Llow≤35nm (1-2)

[0019] (2) The light absorption anisotropic film according to (1) above, wherein:

[0020] In the cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in the central 150 nm region C in the film thickness direction is set to Lmi d, the above-mentioned light absorption anisotropic film preferably satisfies at least one of the following formulas (2-1) and (2-2).

[0021] Ltop / Lmid<0.87 (2-1)

[0022] Llow / Lmid<0.87 (2-2)

[0023] (3) The light absorption anisotropic film according to (1) or (2) above, which satisfies the following formula (3-1).

[0024] Lmid>40nm (3-1)

[0025] (4) The light absorption anisotropic film according to any one of (1) to (3) above, comprising a substance with localized distribution that is localized in at least one of the region A and the region B.

[0026] (5) The light absorption anisotropic film according to (4) above, wherein

[0027] The weight average molecular weight of the above-mentioned partial existence substance is 1,000 or more.

[0028] (6) A method for producing the light absorption anisotropic film according to any one of (1) to (5), comprising:

[0029] a coating film forming step of forming a coating film by coating a light absorption anisotropic film-forming composition containing a dichroic substance and a liquid crystal compound on the alignment film; and

[0030] In the orientation step, the dichroic material contained in the coating film is oriented to obtain a light absorption anisotropic film.

[0031] (7) The manufacturing method according to (6) above, wherein:

[0032] The above-mentioned alignment step includes a step of exposing the above-mentioned coating film in the atmosphere.

[0033] (8) The manufacturing method according to (6) or (7) above, wherein:

[0034] The alignment step includes exposing the coating film to ultraviolet light that does not include light having a wavelength of 330 nm or more.

[0035] (9) A laminate comprising the light absorption anisotropic film according to any one of (1) to (5) above and a λ / 4 plate.

[0036] (10) An image display device comprising the light absorption anisotropic film according to any one of (1) to (5) above.

[0037] Effects of the Invention

[0038] As described below, according to the present invention, it is possible to provide a light absorption anisotropic film that exhibits excellent black contrast when used in an image display device, a method for producing the same, and a laminate and an image display device having the light absorption anisotropic film. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 1 is a schematic partial cross-sectional view of a light anisotropic absorption film 100 which is one embodiment of the light anisotropic absorption film of the present invention. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in detail.

[0041] The description of the constituent elements described below is made based on typical embodiments of the present invention, but the present invention is not limited to these embodiments.

[0042] In addition, in this specification, the numerical range expressed using "to" indicates a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0043] Furthermore, in this specification, parallel, orthogonal, horizontal and vertical respectively represent the range of parallel ±10°, the range of orthogonal ±10°, the range of horizontal ±10° and the range of vertical ±10°, and do not respectively represent parallel, orthogonal, horizontal and vertical in the strict sense.

[0044] In addition, in this specification, for each component, one substance corresponding to each component may be used alone, or two or more substances may be used simultaneously. Here, when two or more substances are used simultaneously for each component, the content of the component refers to the total content of the substances used simultaneously unless otherwise specified.

[0045] Furthermore, regarding the light absorption anisotropic film, being excellent in black contrast, durability, heat resistance, and orientation degree is also referred to as “excellent in the effects of the present invention, etc.”

[0046] Furthermore, in this specification, “(meth)acrylate” means “acrylate” or “methacrylate”, “(meth)acryl” means “acryl” or “methacryl”, and “(meth)acryloyl” means “acryloyl” or “methacryloyl”.

[0047] [1] Light absorption anisotropic film

[0048] The light absorption anisotropic film of the present invention contains a dichroic substance and a liquid crystal compound, wherein:

[0049] At least a portion of the dichroic material forms an array structure,

[0050] In a cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in region A from one surface to 150 nm in the film thickness direction is set to Ltop and the average value of the length of the major axis of the arrangement structure observed in region B from another surface to 150 nm in the film thickness direction is set to Llow, the above-mentioned light absorption anisotropic film (hereinafter also referred to as "the film of the present invention") satisfies at least one of the following formula (1-1) and the following formula (1-2).

[0051] Ltop≤35nm (1-1)

[0052] Llow≤35nm (1-2)

[0053] The film of the present invention has such a structure, and therefore is considered to be able to solve the above-mentioned problems of the present invention. Although the reason is not clear, it is presumed that the size of the arrangement structure near the surface of the film of the present invention is small, and external light is less likely to be scattered when incident.

[0054] In the film of the present invention, dichroic substances, liquid crystal compounds, or a dichroic substance and a liquid crystal compound may be bonded via a crosslinking group, a polymerizable group, or the like.

[0055] Hereinafter, the arrangement structure will be described first, and then each component contained in the film will be described.

[0056] [Arrangement structure]

[0057] In the light absorption anisotropic film of the present invention, at least a part of the above-mentioned dichroic substance forms an aligned structure.

[0058] Here, the arrangement structure refers to a state in which the dichroic substance is aggregated to form an aggregate in the light absorption anisotropic film, and the molecules of the dichroic substance are periodically arranged in the aggregate.

[0059] Furthermore, the alignment structure may be formed of only the dichroic substance, or may be formed of the liquid crystal compound and the dichroic substance.

[0060] Furthermore, the arrangement structure may be formed of one dichroic substance or may be formed of a plurality of dichroic substances.

[0061] Furthermore, in the arrangement structure, an aggregate formed of a certain type of dichroic substance and an aggregate formed of another type of dichroic substance may exist in a mixed state in the light absorption anisotropic film.

[0062] Furthermore, when the light absorption anisotropic film contains a plurality of dichroic substances, all or part of the plurality of dichroic substances contained in the light absorption anisotropic film may form an array structure.

[0063] [Dimensions of the array structure]

[0064] 〔Region A, Region B and Region C〕

[0065] First, the region A, the region B, and the region C of the optically anisotropic absorption film of the present invention will be described.

[0066] Figure 1 1 is a schematic partial cross-sectional view of a light anisotropic absorption film 100 which is one embodiment of the light anisotropic absorption film of the present invention.

[0067] like Figure 1As shown, region A is a region from one surface a to 150 nm in the film thickness direction. Also, region B is a region from another surface b to 150 nm in the film thickness direction. Also, region C is a region of the central 150 nm in the film thickness direction, in other words, a region consisting of a region from the central c in the film thickness direction to 75 nm in the film thickness direction (surface a) and a region from the central c in the film thickness direction to 75 nm in the film thickness direction (surface b).

[0068] In addition, in this specification, when the light absorption anisotropic film is a film produced by applying a light absorption anisotropic film-forming composition containing a dichroic substance and a liquid crystal compound to a substrate (e.g., an oriented film), the area on the coating surface side is referred to as area A, and the area on the substrate side is referred to as area B.

[0069] [Formula (1-1) and formula (1-2)]

[0070] In a cross section observed by a scanning transmission electron microscope, when the average value of the length L of the major axis of the arrangement structure observed in region A from one surface to 150 nm in the film thickness direction is set to Ltop and the average value of the length of the major axis of the arrangement structure observed in region B from another surface to 150 nm in the film thickness direction is set to Llow, the film of the present invention satisfies at least one of the following formulas (1-1) and (1-2).

[0071] Ltop≤35nm (1-1)

[0072] Llow≤35nm (1-2)

[0073] From the viewpoint of more excellent effects of the present invention, Ltop and Llow are each independently preferably 30 nm or less, and more preferably 25 nm or less.

[0074] The lower limits of Ltop and Llow are not particularly limited, but are each independently preferably 5 nm or more, more preferably 7 nm or more, and further preferably 10 nm or more, for reasons of superior effects of the present invention and the like.

[0075] <Method>

[0076] (Formula (1-1))

[0077] As a method for making the light absorption anisotropic film satisfy the formula (1-1), for example, a method of further adding a surfactant and a substance having a high affinity for the surfactant (for example, a small LogP value (octanol / water partition coefficient)) and a high molecular weight (for example, Mw of 1,000 or more) to the light absorption anisotropic film-forming composition in the production method (coating film forming step, orientation step) of the present invention described later can be cited. In this case, in the formed coating film, the surfactant is preferentially present on the coating surface side, and accompanying this, the substance is also preferentially present in the region A on the coating surface side due to the affinity with the surfactant. That is, the substance functions as a preferentially present substance that is preferentially present in the region A. Moreover, the preferentially present substance with a high molecular weight is preferentially present in the region A, thereby increasing the viscosity of the region A and reducing the formation speed of the arrangement structure of the dichroic substance in the region A. As a result, a light absorption anisotropic film having a small size (Ltop) of the arrangement structure in the region A can be obtained. In addition, the value of Ltop can be further adjusted according to the type, molecular weight, and amount of the preferred substance.

[0078] Another method for making the light absorption anisotropic film satisfy the formula (1-1) is, for example, a method of exposing the coating film to short-wavelength UV light as described later (preferable aspect 2).

[0079] (Formula (1-2))

[0080] Furthermore, as a method for making the light absorbing anisotropic film satisfy the formula (1-2), for example, a method can be cited in which a substance having a small ΔSP value (difference in solubility parameter) and a high molecular weight (for example, Mw of 1,000 or more) relative to the substrate (for example, an oriented film) of the coating composition is further added to the light absorbing anisotropic film-forming composition in the manufacturing method of the present invention described later. In this case, in the formed coating film, the above-mentioned substance will be biased to exist in the region B on the substrate surface side due to its affinity with the substrate. That is, the above-mentioned substance functions as a biased substance that is biased to exist in the region B. Moreover, the biased substance with a high molecular weight is biased to exist in the region B, thereby increasing the viscosity of the region B and reducing the formation speed of the arrangement structure of the dichroic substance in the region B. As a result, a light absorbing anisotropic film having a small size (Llow) of the arrangement structure of the region B can be obtained. In addition, the value of Llow can be further adjusted according to the type, molecular weight, addition amount, etc. of the biased substance.

[0081] Another method for making the light absorption anisotropic film satisfy the formula (1-2) is, for example, a method of exposing a coating film to light in the atmosphere described later (preferable aspect 1).

[0082] [Formula (2-1) and formula (2-2)]

[0083] Considering the reason that the effects of the present invention (especially durability and heat resistance) are more excellent, in the cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in the central 150nm region C in the film thickness direction is set to Lmid, the film of the present invention preferably satisfies at least one of the following formulas (2-1) and (2-2). The definitions of Ltop and Llow are as described above.

[0084] Ltop / Lmid<0.87 (2-1)

[0085] Llow / Lmid<0.87 (2-2)

[0086] From the perspective of achieving more excellent effects of the present invention (particularly durability and heat resistance), Ltop / Lmid and Llow / Lmid are each independently preferably 0.70 or less, more preferably 0.60 or less, and further preferably 0.50 or less.

[0087] The lower limits of Ltop / Lmid and Llow / Lmid are not particularly limited, but are each independently preferably 0.10 or more, more preferably 0.20 or more, and further preferably 0.30 or more, for reasons of superior effects of the present invention.

[0088] <Method>

[0089] As a method for making the light absorption anisotropic film satisfy the formula (2-1) or the formula (2-2), for example, the same method as the method for satisfying the above-mentioned formula (1-1) or the formula (1-2) can be cited. That is, by making Ltop or Llow relatively smaller than Lmid, as a result, a light absorption anisotropic film satisfying the formula (2-1) or the formula (2-2) can be obtained.

[0090] [Formula (3-1)]

[0091] The film of the present invention preferably satisfies the following formula (3-1) because the effects of the present invention and the like (particularly durability and heat resistance) are more excellent. The definition of Lmid is as described above.

[0092] Lmid>40nm (3-1)

[0093] From the viewpoint that the effects of the present invention (particularly durability and heat resistance) are more excellent, Lmid is preferably 50 nm or more.

[0094] The upper limit of Lmid is not particularly limited, but is preferably 100 nm or less, more preferably 80 nm or less, from the perspective of achieving the effects of the present invention and other reasons.

[0095] <Method>

[0096] As a method for making the light absorption anisotropic film satisfy the formula (3-1), for example, the production method of the present invention described later can be cited.

[0097] 〔Observation of cross section〕

[0098] Next, observation of the cross section using a scanning transmission electron microscope will be described.

[0099] In the present invention, observation of a cross section using a scanning transmission electron microscope (Scanning Transmission Electron Microscope) (hereinafter also referred to as “STEM”) is specifically performed as follows.

[0100] First, the light absorption anisotropic film was sliced ​​in the film thickness direction using an ultra-microtome, thereby preparing an ultra-thin slice with a thickness of 100 nm.

[0101] Next, the ultrathin sections were placed on a grid with a carbon support film for STEM observation.

[0102] Thereafter, each grid was placed in a scanning transmission electron microscope, and a cross section was observed at an electron beam acceleration voltage of 30 kV.

[0103] [Measurement of the length L of the major axis]

[0104] And, specifically, the length L of the major axis of the array structure is measured as follows.

[0105] First, as described above, a cross section of the light absorption anisotropic film is observed by STEM, the captured image is analyzed, a frequency histogram is prepared, and the frequency at which the frequency becomes the maximum and the standard deviation of the frequency distribution are obtained. Next, the frequency at which the frequency becomes the maximum to the dark side becomes 1.3 times the standard deviation is set as a threshold. Next, an image is prepared in which the brightness is binarized using the threshold, an ellipse is approximated for the dark area after binarization, and the length of the major axis of the approximated ellipse is taken as the length L of the major axis of the arrangement structure.

[0106] The length L of the major axis of the array structure may be measured using known image processing software. For example, the image processing software "ImageJ" can be exemplified.

[0107] The above-described image analysis was performed on each region (region A, region B, and region C), and the image was analyzed at 13.58 μm arbitrarily selected non-overlapping regions. 2 area, 3 locations (40 μm in total) 2 ), the arrangement structures satisfying L ≥ 5 nm are extracted and counted.

[0108] In the arbitrarily selected non-overlapping 40 μm 2 (13.58μm 2 Such arrangement structures were counted in the region of ×3) and 10 sites.

[0109] On this basis, for each region, the average value of the length of the major axis of the array structure at the 10 locations measured was calculated, and the average value was set as Ltop (region A), Llow (region B), and Lmid (region C).

[0110] In fact, the measured value is 13.58 μm. 2 ×3=40.74μm 2 However, in the present invention, for the sake of convenience, the decimal point is discarded and referred to as "every 40 μm 2 ”.

[0111] [Dichroic substances]

[0112] The dichroic substances contained in the film of the present invention are not particularly limited. For example, visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet absorbing substances, infrared absorbing substances, nonlinear optical substances, carbon nanotubes and inorganic substances (for example, quantum rods) can be mentioned. Conventionally known dichroic substances (dichroic pigments) can be used.

[0113] For example, paragraphs

[0067] to

[0071] of Japanese Patent Application Laid-Open No. 2013-228706, paragraphs

[0008] to

[0026] of Japanese Patent Application Laid-Open No. 2013-227532, paragraphs

[0008] to

[0015] of Japanese Patent Application Laid-Open No. 2013-209367, paragraphs

[0045] to

[0058] of Japanese Patent Application Laid-Open No. 2013-014883, paragraphs

[0012] to

[0029] of Japanese Patent Application Laid-Open No. 2013-109090, and paragraphs

[0013] to

[0029] of Japanese Patent Application Laid-Open No. 2013-101328.

[0009] to

[0017] , paragraphs

[0051] to

[0065] of Japanese Patent Application Publication No. 2013-037353, paragraphs

[0049] to

[0073] of Japanese Patent Application Publication No. 2012-063387, paragraphs

[0016] to

[0018] of Japanese Patent Application Publication No. 11-305036, paragraphs

[0009] to

[0011] of Japanese Patent Application Publication No. 2001-133630, paragraphs

[0030] to

[0169] of Japanese Patent Application Publication No. 2011-215337, Japanese Patent Application Publication No. 2010-10624 2, paragraphs

[0021] to

[0075] of Japanese Patent Publication No. 2010-215846, paragraphs

[0011] to

[0025] of Japanese Patent Publication No. 2011-048311, paragraphs

[0013] to

[0133] of Japanese Patent Publication No. 2011-213610, paragraphs

[0074] to

[0246] of Japanese Patent Publication No. 2011-237513, paragraphs

[0005] to

[0051] of Japanese Patent Publication No. 2016-006502, WO2016 Substances described in paragraphs

[0005] to

[0041] of WO 2016 / 060173, paragraphs

[0008] to

[0062] of WO 2016 / 136561, paragraphs

[0014] to

[0033] of International Publication No. 2017 / 154835, paragraphs

[0014] to

[0033] of International Publication No. 2017 / 154695, paragraphs

[0013] to

[0037] of International Publication No. 2017 / 195833, and paragraphs

[0014] to

[0034] of International Publication No. 2018 / 164252.

[0114] In the film of the present invention, two or more dichroic substances may be used simultaneously. For example, from the viewpoint of making the obtained light absorption anisotropic film closer to black, it is preferred to simultaneously use at least one dichroic substance having a maximum absorption wavelength in the range of 370 nm to less than 500 nm and at least one dichroic substance having a maximum absorption wavelength in the range of 500 nm to less than 700 nm.

[0115] The above-mentioned dichroic substance may have a crosslinkable group.

[0116] Examples of the crosslinkable group include a (meth)acryloyl group, an epoxy group, an oxetanyl group, and a styryl group. Among them, a (meth)acryloyl group is preferred because the effects of the present invention and the like are more excellent.

[0117] 〔content〕

[0118] In the film of the present invention, the content of the dichroic substance is preferably 2 to 80 parts by mass, more preferably 10 to 60 parts by mass, and even more preferably 15 to 40 parts by mass based on 100 parts by mass of the liquid crystal compound described below, because the effects of the present invention are more excellent.

[0119] In the film of the present invention, the content of the dichroic substance is preferably 1 to 50% by mass, more preferably 5 to 40% by mass, and even more preferably 10 to 30% by mass, because the effects of the present invention and the like are more excellent.

[0120] [Liquid Crystalline Compounds]

[0121] As the liquid crystal compound contained in the film of the present invention, any of a polymer liquid crystal compound and a low molecular liquid crystal compound can be used, but a polymer liquid crystal compound is preferably used from the viewpoint of further increasing the degree of orientation of the dichroic substance.

[0122] Here, the "polymer liquid crystal compound" refers to a liquid crystal compound having a repeating unit in its chemical structure.

[0123] Furthermore, the “low-molecular liquid crystal compound” refers to a liquid crystal compound having no repeating unit in its chemical structure.

[0124] Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymer described in JP-A-2011-237513 and the polymer liquid crystal compound described in paragraphs

[0012] to

[0042] of WO-2018 / 199096.

[0125] Examples of the low-molecular liquid crystal compound include the liquid crystal compounds described in paragraphs

[0072] to

[0088] of JP-A-2013-228706, and among these, liquid crystal compounds showing smecticity are preferred.

[0126] Furthermore, as the liquid crystal compound, a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound may be used simultaneously.

[0127] When a polymer liquid crystal compound and a liquid crystal compound are used simultaneously, the ratio of the polymer liquid crystal compound to the liquid crystal compound as a whole is preferably 30 to 85% by mass, more preferably 45 to 80% by mass, and further preferably 60 to 75% by mass, for reasons of superior effects of the present invention.

[0128] [Preferred method]

[0129] As the liquid crystal compound, a polymer liquid crystal compound including a repeating unit represented by the following formula (1) (hereinafter, also simply referred to as “repeating unit (1)”) is preferred from the viewpoint of increasing the degree of orientation of the dichroic substance.

[0130] [Chemical formula 1]

[0131]

[0132] In the above formula (1), P1 represents the main chain of the repeating unit, L1 represents a single bond or a divalent linking group, SP1 represents a spacer group, M1 represents a mesogen group, and T1 represents a terminal group.

[0133] Examples of the main chain of the repeating unit represented by P1 include groups represented by the following formulae (P1-A) to (P1-D). Among them, the group represented by the following formula (P1-A) is preferred from the viewpoint of the diversity of monomers used as raw materials and easy handling.

[0134] [Chemical formula 2]

[0135]

[0136] In the above formulae (P1-A) to (P1-D), "*" indicates a bonding position with L1 in the above formula (1).

[0137] In the above formulas (P1-A) to (P1-D), R 1 , R 2 , R 3 and R 4 Each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. The alkyl group may be a linear or branched alkyl group, or an alkyl group having a cyclic structure (cycloalkyl group). The alkyl group preferably has 1 to 5 carbon atoms.

[0138] The group represented by the above formula (P1-A) is preferably a unit of a partial structure of a poly(meth)acrylate obtained by polymerization of a (meth)acrylate.

[0139] The group represented by the above formula (P1-B) is preferably an ethylene glycol unit formed by ring-opening polymerization of an epoxy group of a compound having an epoxy group.

[0140] The group represented by the above formula (P1-C) is preferably a propylene glycol unit formed by ring-opening polymerization of an oxetane group of a compound having an oxetane group.

[0141] The group represented by the above formula (P1-D) is preferably a siloxane unit of a polysiloxane obtained by condensation polymerization of a compound having at least one of an alkoxysilyl group and a silanol group. Here, examples of the compound having at least one of an alkoxysilyl group and a silanol group include a compound having the formula SiR 4 (OR 5 )2-represented by a group. In the formula, R 4 The meaning is the same as R in (P1-D) 4 The same meaning, multiple R 5 Each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.

[0142] In the above formula (1), L1 is a single bond or a divalent linking group.

[0143] Examples of the divalent linking group represented by L1 include -C(O)O-, -O-, -S-, and -C(O)NR 6 -, -SO2-, and -NR 6 R 7 -. In the formula, R 6 and R 7 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent.

[0144] When P1 is a group represented by the formula (P1-A), L1 is preferably a group represented by -C(O)O- from the viewpoint that the degree of orientation of the dichroic substance becomes higher.

[0145] When P1 is a group represented by formula (P1-B) to (P1-D), L1 is preferably a single bond from the viewpoint of increasing the degree of orientation of the dichroic substance.

[0146] In the above formula (1), the spacer represented by SP1 preferably includes at least one structure selected from the group consisting of an oxyethylene structure, an oxypropylene structure, a polysiloxane structure and a fluorinated alkylene structure from the viewpoint of easy expression of liquid crystallinity and availability of raw materials.

[0147] Here, the oxyethylene structure represented by SP1 is preferably *-(CH2-CH2O) n1- a group represented by *. In the formula, n1 represents an integer of 1 to 20, and * represents the bonding position to L1 or M1 in the above formula (1). From the viewpoint of increasing the degree of orientation of the dichroic substance, n1 is preferably an integer of 2 to 10, more preferably an integer of 2 to 4, and most preferably 3.

[0148] Furthermore, from the viewpoint of increasing the degree of orientation of the dichroic substance, the oxypropylene structure represented by SP1 is preferably composed of *-(CH(CH3)-CH2O) n2 - A group represented by *. In the formula, n2 represents an integer of 1 to 3, and * represents a bonding position to L1 or M1.

[0149] Furthermore, from the viewpoint of increasing the degree of orientation of the dichroic substance, the polysiloxane structure represented by SP1 is preferably composed of *-(Si(CH3)2-O) n3 - A group represented by *. In the formula, n3 represents an integer of 6 to 10, and * represents a bonding position with L1 or M1.

[0150] Furthermore, from the viewpoint of increasing the degree of orientation of the dichroic substance, the fluorinated alkylene structure represented by SP1 is preferably composed of *-(CF2-CF2) n4 - A group represented by *. In the formula, n4 represents an integer of 6 to 10, and * represents a bonding position to L1 or M1.

[0151] In the above formula (1), the mesogen group represented by M1 refers to a group representing the main skeleton of the liquid crystal molecule that helps to form the liquid crystal. The liquid crystal molecule shows liquid crystal properties in an intermediate state (intermediate phase) between the crystalline state and the isotropic liquid state. There is no particular limitation on the mesogen group, and for example, reference can be made to "Flussige Kristalle in Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, 1999, 2000), especially the records in Chapter 3.

[0152] As the mesogenic group, for example, a group having at least one cyclic structure selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group is preferred.

[0153] From the viewpoint of increasing the degree of orientation of the dichroic substance, the mesogen group preferably has an aromatic hydrocarbon group, more preferably has 2 to 4 aromatic hydrocarbon groups, and even more preferably has 3 aromatic hydrocarbon groups.

[0154] As the mesogen group, from the perspective of the manifestation of liquid crystal properties, adjustment of the liquid crystal phase transition temperature, raw material availability and synthetic adaptability, and the viewpoint of a higher degree of orientation of the dichroic substance, a group represented by the following formula (M1-A) or the following formula (M1-B) is preferred, and a group represented by the formula (M1-B) is more preferred.

[0155] [Chemical formula 3]

[0156]

[0157] In formula (M1-A), A1 is a divalent group selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group. These groups may be substituted with an alkyl group, a fluorinated alkyl group, an alkoxy group, or a substituent.

[0158] The divalent group represented by A1 is preferably a 4- to 6-membered ring. Furthermore, the divalent group represented by A1 may be a monocyclic ring or a condensed ring.

[0159] * indicates the bonding position to SP1 or T1.

[0160] Examples of the divalent aromatic hydrocarbon group represented by A1 include phenylene, naphthylene, fluorene-diyl, anthracene-diyl and tetracene-diyl. From the viewpoint of the diversity of the design of the mesogen skeleton and the availability of raw materials, phenylene or naphthylene is preferred, and phenylene is more preferred.

[0161] The divalent heterocyclic group represented by A1 may be either aromatic or non-aromatic, but is preferably a divalent aromatic heterocyclic group from the viewpoint of increasing the degree of orientation of the dichroic substance.

[0162] Examples of atoms other than carbon constituting the divalent aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms other than carbon constituting the ring, these atoms may be the same or different.

[0163] Examples of the divalent aromatic heterocyclic group include a pyridylene group (pyridine-diyl), a pyridazine-diyl group, an imidazole-diyl group, a thiophene-diyl group (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimide-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group, and a thieno-oxazole-diyl group.

[0164] Examples of the divalent alicyclic group represented by A1 include a cyclopentylene group and a cyclohexylene group.

[0165] In the formula (M1-A), a1 represents an integer of 1 to 10. When a1 is 2 or more, a plurality of A1s may be the same or different.

[0166] In formula (M1-B), A2 and A3 are each independently a divalent group selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group. Specific examples and preferred embodiments of A2 and A3 are the same as those of A1 in formula (M1-A), and thus description thereof is omitted.

[0167] In formula (M1-B), a2 represents an integer of 1 to 10. When a2 is 2 or more, multiple A2s may be the same or different, multiple A3s may be the same or different, and multiple LA1s may be the same or different. From the viewpoint of increasing the degree of orientation of the dichroic substance, a2 is preferably an integer of 2 or more, and more preferably 2.

[0168] In formula (M1-B), when a2 is 1, LAl is a divalent linking group. When a2 is 2 or more, a plurality of LAls are independently a single bond or a divalent linking group, and at least one of the plurality of LAls is a divalent linking group. When a2 is 2, from the viewpoint that the orientation degree of the dichroic substance becomes higher, it is preferred that one of the two LAls is a divalent linking group and the other is a single bond.

[0169] In the formula (M1-B), examples of the divalent linking group represented by LA1 include -O-, -(CH2) g -、-(CF2) g -、-Si(CH3)2-、-(Si(CH3)2O) g -、-(OSi(CH3)2) g-(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2-C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O)O-, -N(Z)C(O)-, -C (O)N(Z)-, -C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)=C(Z')-C(O)N(Z”)-, -N(Z”)-C(O)-C(Z)=C(Z’)-,- C(Z)=C(Z')-C(O)-S-, -SC(0)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')-(Z, Z', Z" each independently represent a hydrogen atom, a C1-C4 alkyl group, a cycloalkyl group, an aryl group, a cyano group or a halogen atom.), -C≡C-, -N=N-, -S-, -S(O)-, -S(O)(O)-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)- and -C(O)S-. Among them, from the viewpoint of making the orientation degree of the dichroic substance higher, -C(O)O- is preferred. LA1 may also be a group formed by combining two or more of these groups.

[0170] In the above formula (1), examples of the terminal group represented by T1 include a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxyl group, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an alkoxycarbonyloxy group having 1 to 10 carbon atoms, an alkoxycarbonyl group having 1 to 10 carbon atoms (ROC(O)-: R is an alkyl group), an acyloxy group having 1 to 10 carbon atoms, an acylamino group having 1 to 10 carbon atoms, an alkoxycarbonylamino group having 1 to 10 carbon atoms, a sulfonylamino group having 1 to 10 carbon atoms, a sulfamoyl group having 1 to 10 carbon atoms, a carbamoyl group having 1 to 10 carbon atoms, a sulfinyl group having 1 to 10 carbon atoms, a ureido group having 1 to 10 carbon atoms, and a (meth)acryloyloxy-containing group. Examples of the group containing a (meth)acryloyloxy group include a group represented by -LA (L represents a single bond or a linking group. Specific examples of the linking group are the same as those of L1 and SP1 described above. A represents a (meth)acryloyloxy group).

[0171] From the viewpoint of increasing the degree of orientation of the dichroic substance, T1 is preferably an alkoxy group having 1 to 10 carbon atoms, more preferably an alkoxy group having 1 to 5 carbon atoms, and still more preferably a methoxy group.

[0172] These terminal groups may be further substituted with these groups or polymerizable groups described in JP-A-2010-244038.

[0173] From the viewpoint of further improving the adhesion between the polarizer (light absorption anisotropic film) and the optical anisotropic layer and improving the cohesive force of the film, T1 is preferably a polymerizable group.

[0174] The polymerizable group is preferably a radical polymerizable group or a cation polymerizable group.

[0175] As the free radical polymerizable group, a well-known free radical polymerizable group can be used, preferably an acryloyl group or a methacryloyl group. In this case, it is known that the polymerization rate of the acryloyl group is generally faster, and from the viewpoint of improving productivity, an acryloyl group is preferably used, but a methacryloyl group can also be used as a polymerizable group in the same manner.

[0176] As the cationically polymerizable group, a commonly known cationically polymerizable group can be used, for example, an alicyclic ether group, a cyclic acetal group, a cyclic lactone group, a cyclic thioether group, a spirocyclic orthoester group, and a vinyloxy group can be mentioned. Among them, an alicyclic ether group or a vinyloxy group is preferred, and an epoxy group, an oxetane group, or a vinyloxy group is more preferred.

[0177] <Molecular weight>

[0178] The weight average molecular weight (Mw) of the polymer liquid crystal compound containing the repeating unit represented by the above formula (1) is preferably 1000 to 500000, more preferably 2000 to 300000. When the Mw of the polymer liquid crystal compound is within the above range, the polymer liquid crystal compound can be easily handled.

[0179] In particular, from the viewpoint of suppressing cracking during coating, the weight average molecular weight (Mw) of the polymer liquid crystal compound is preferably 10,000 or more, and more preferably 10,000 to 300,000.

[0180] Furthermore, from the viewpoint of the temperature tolerance of the orientation degree, the weight average molecular weight (Mw) of the polymer liquid crystal compound is preferably less than 10,000, and preferably 2,000 or more and less than 10,000.

[0181] In addition, in this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values ​​measured by gel permeation chromatography (GPC) method.

[0182] Solvent (eluent): N-methylpyrrolidone

[0183] Device name: TOSOH HLC-8220GPC

[0184] Column: 3 TOSOH TSKgelSuperAWM-H (6mm×15cm) connected and used

[0185] Column temperature: 25℃

[0186] Sample concentration: 0.1 mass%

[0187] Flow rate: 0.35ml / min

[0188] Calibration curve: Calibration curve of seven samples with Mw=2800000 to 1050 (Mw / Mn=1.03 to 1.06) based on TSK standard polystyrene manufactured by TOSOH

[0189] 〔content〕

[0190] In the film of the present invention, from the effect of the present invention and other more excellent reasons, the content of the liquid crystal compound is preferably 50 mass % or more, more preferably 70 mass % or more. The upper limit of the content of the liquid crystal compound is not particularly limited, but from the effect of the present invention and other more excellent reasons, preferably 95 mass % or less.

[0191] [Other ingredients]

[0192] The film of the present invention may contain other components in addition to the above-mentioned dichroic substance and liquid crystal compound. Examples of such other components include localized substances, polymerization initiators, surfactants, and the like.

[0193] 〔Biased towards existential matter〕

[0194] Considering the reasons that Ltop or Llow becomes smaller and the effect of the present invention is more excellent, one of the preferred embodiments of the film of the present invention is to contain a substance with partial existence that is partial to at least one of region A and region B. The substance with partial existence may also be present in a region other than region A and region B (for example, region C). Specific examples and preferred embodiments of the substance with partial existence are described below.

[0195] <Content>

[0196] In the film of the present invention, the content of the biased substance is preferably 0.5 mass % or more, more preferably 1.0 mass % or more, and further preferably 1.5 mass % or more, because Ltop or Llow becomes smaller and the effects of the present invention are more excellent.

[0197] In the film of the present invention, the content of the localized substance is preferably 3.0% by mass or less, and more preferably 2.5% by mass or less, because the effects of the present invention and the like are more excellent.

[0198] [thickness]

[0199] The thickness of the light absorption anisotropic film is not particularly limited, but is preferably 300 to 8000 nm, more preferably 450 to 5000 nm, and further preferably 1000 to 3000 nm because the effects of the present invention are more excellent.

[0200] The thickness of the light absorption anisotropic film refers to the average thickness of the light absorption anisotropic film. The average thickness is determined by measuring the thickness of five or more arbitrary locations of the light absorption anisotropic film and taking the arithmetic average of the thicknesses.

[0201] [2] Method for manufacturing anisotropic light absorption film

[0202] The method for producing the above-mentioned light absorption anisotropic film of the present invention is not particularly limited, but from the reason that the effects of the present invention and the like are more excellent for the obtained light absorption anisotropic film, a production method including the following steps (hereinafter also referred to as "the production method of the present invention") is preferred. In addition, hereinafter, the case where the effects of the present invention and the like are excellent for the obtained light absorption anisotropic film is also simply referred to as "the effects of the present invention and the like are excellent".

[0203] (1) Coating film forming step

[0204] Step of forming a coating film by applying a light absorption anisotropic film-forming composition containing a dichroic substance and a liquid crystal compound onto an alignment film

[0205] (2) Orientation process

[0206] A step of obtaining a light absorption anisotropic film by orienting the dichroic substance contained in the above-mentioned coating film.

[0207] Hereinafter, each step will be described.

[0208] [Coating film forming step]

[0209] The coating film forming step is a step of forming a coating film (coating film) by applying a light absorption anisotropic film-forming composition containing a dichroic substance and a liquid crystal compound onto the alignment film.

[0210] By using a light absorbing anisotropic film-forming composition containing a solvent or by using a composition obtained by melting the light absorbing anisotropic film-forming composition by heating or the like in a liquid state such as a melt, the light absorbing anisotropic film-forming composition can be easily applied to the alignment film.

[0211] Examples of the coating method for the light absorption anisotropic film-forming composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet.

[0212] [Light-absorbing anisotropic film-forming composition]

[0213] The light absorption anisotropic film-forming composition used in the coating film forming step is a composition containing a dichroic substance and a liquid crystal compound (hereinafter, also referred to as “the composition of the present invention”).

[0214] The composition of the present invention may contain other components in addition to the dichroic substance and the liquid crystal compound. Examples of such other components include localized substances, polymerization initiators, surfactants, solvents, and the like.

[0215] <Dichroic substances>

[0216] The composition of the present invention contains a dichroic substance. Specific examples and preferred embodiments of the dichroic substance are as described above.

[0217] (content)

[0218] In the composition of the present invention, the content of the dichroic substance is preferably 2 to 80 parts by mass, more preferably 10 to 60 parts by mass, and further preferably 20 to 40 parts by mass based on 100 parts by mass of the liquid crystal compound, because the effects of the present invention are more excellent.

[0219] In the composition of the present invention, the content of the dichroic substance is preferably 1 to 50% by mass, more preferably 10 to 40% by mass, and even more preferably 15 to 30% by mass in the total solid content because the effects of the present invention are more excellent.

[0220] In the present specification, the term "solid content" refers to components other than the solvent in the composition, and specific examples of the solid content include liquid crystal compounds, dichroic substances, localized substances, polymerization initiators, and surfactants.

[0221] <Liquid Crystalline Compound>

[0222] The composition of the present invention contains a liquid crystal compound. Specific examples and preferred embodiments of the liquid crystal compound are as described above.

[0223] (content)

[0224] In the composition of the present invention, from the perspective of the effect of the present invention, the content of the liquid crystal compound is preferably 50% by mass or more, more preferably 70% by mass or more in the total solids. The upper limit of the content of the liquid crystal compound is not particularly limited, but from the perspective of the effect of the present invention, the content is preferably 95% by mass or less in the total solids.

[0225] <Biased Existential Matter>

[0226] One of the preferred embodiments of the composition of the present invention is to contain a substance having localized existence because Ltop or Llow becomes smaller and the effects of the present invention are more excellent.

[0227] From the viewpoint of sufficiently increasing the viscosity of the region where the localizing substance is localized in the coating film and improving phase separation, the localizing substance is preferably a polymer, and its weight average molecular weight (Mw) is preferably 1,000 or more, more preferably 5,000 or more.

[0228] The upper limit of the Mw of the partial existence substance is not particularly limited, but is preferably 10,000,000 or less, and more preferably 1,000,000 or less, because the effects of the present invention are more excellent.

[0229] From the viewpoint of orientation, the preferentially localized substance preferably does not include a low surface energy structure (for example, a fluorine atom or a siloxane structure) such as that included in a general surfactant.

[0230] Specific examples of the preferentially existing substance include polyalkylene oxides (especially polyethylene oxide), epoxy resins (especially cresol novolac-type epoxy resins), and the like.

[0231] (content)

[0232] When the composition of the present invention contains a preferentially existing substance, from the viewpoint of sufficiently increasing the viscosity of the region in the coating film where the preferentially existing substance is preferentially existing, the content of the preferentially existing substance is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and further preferably 1.5% by mass or more in the total solid component.

[0233] In the film of the present invention, the content of the localized substance is preferably 3.0% by mass or less, more preferably 2.5% by mass or less in the total solid content, because the effects of the present invention and the like are more excellent.

[0234] <Polymerization Initiator>

[0235] The composition of the present invention preferably contains a polymerization initiator because the effects of the present invention and the like are more excellent.

[0236] The polymerization initiator is not particularly limited, but is preferably a photosensitive compound, that is, a photopolymerization initiator, because the effects of the present invention are more excellent.

[0237] As the photopolymerization initiator, various compounds can be used without particular limitation. As the photopolymerization initiator, for example, α-carbonyl compounds (U.S. Patent No. 2367661, U.S. Patent No. 2367670), acyloin ethers (U.S. Patent No. 2448828), α-hydrocarbon-substituted aromatic acyloin compounds (U.S. Patent No. 2722512), polynuclear quinone compounds (U.S. Patent No. 3046127 and U.S. Patent No. 2951758), a combination of a triaryl imidazole dimer and p-aminophenyl ketone (U.S. Patent No. 3549367) can be cited. ), acridine and phenazine compounds (Japanese Patent Publication No. 60-105667, U.S. Patent No. 4239850), oxadiazole compounds (U.S. Patent No. 4212970), o-acyl oxime compounds (Japanese Patent Publication No. 2016-027384

[0065] ) and acylphosphine oxide compounds (Japanese Patent Publication No. 63-040799, Japanese Patent Publication No. 5-029234, Japanese Patent Publication No. 10-095788 and Japanese Patent Publication No. 10-029997), etc.

[0238] (content)

[0239] When the composition of the present invention contains a polymerization initiator, the content of the polymerization initiator is preferably 0.01 to 30 parts by mass, more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the total of the above-mentioned dichroic substance and the above-mentioned liquid crystal compound, because the effects of the present invention are more excellent.

[0240] <Surfactant>

[0241] The composition of the present invention preferably contains a surfactant because the effects of the present invention and the like are more excellent.

[0242] By containing a surfactant, it is expected that the smoothness of the coating surface is improved, the degree of orientation is further improved, or the uniformity within the surface is improved by suppressing recesses and unevenness.

[0243] As a surfactant, a surfactant that makes the dichroic substance and the liquid crystal compound horizontal on the coating surface side is preferred because the effect of the present invention is more excellent. For example, the compounds described in paragraphs

[0155] to

[0170] of International Publication No. 2016 / 009648 and the compounds described in paragraphs

[0253] to

[0293] of Japanese Patent Gazette No. 2011-237513 (horizontal alignment agents) can be cited.

[0244] (content)

[0245] When the composition of the present invention contains a surfactant, the content of the surfactant is preferably 0.001 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, based on 100 parts by mass of the total of the dichroic substance and the liquid crystal compound.

[0246] <Solvent>

[0247] From the viewpoint of workability, the composition of the present invention preferably contains a solvent.

[0248] Examples of the solvent include organic solvents such as ketones, ethers, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, halogenated carbons, esters, alcohols, cellosolves, cellosolve acetates, sulfoxides, amides, and heterocyclic compounds, and water. These solvents may be used alone or in combination of two or more.

[0249] (content)

[0250] When the composition of the present invention contains a solvent, the content of the solvent is preferably 80 to 99% by mass, more preferably 83 to 97% by mass, based on the total mass of the composition, because the effects of the present invention and the like are more excellent.

[0251] 〔Oriented film〕

[0252] The alignment film may be any film as long as it is a film that aligns (for example, horizontally aligns) the liquid crystal compound contained in the composition of the present invention.

[0253] It can be set by the following methods: such as friction treatment of the film surface of an organic compound (preferably a polymer), inclined evaporation of an inorganic compound, formation of a layer with microgrooves, or accumulation of an organic compound (e.g., ω-tricosanoic acid, dioctadecylmethylammonium chloride, methyl stearate) based on the Lamb-Blodgett method (LB film). In addition, it is also known that there are oriented films that produce an orientation function by imparting an electric field, a magnetic field, or light irradiation. Among them, in the present invention, from the viewpoint of easy control of the pretilt angle of the oriented film, an oriented film formed by friction treatment is preferred, and from the viewpoint of uniformity of the orientation, a photo-oriented film formed by light irradiation is also preferred.

[0254] (1) Rubbing treatment of oriented film

[0255] The polymer material used in the alignment film formed by rubbing treatment is described in many documents and is available in many commercial products. In the present invention, polyvinyl alcohol or polyimide and its derivatives are preferably used. For the alignment film, reference can be made to the description on page 43, line 24 to page 49, line 8 of International Publication No. 2001 / 88574A1.

[0256] The thickness of the alignment film is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm.

[0257] (2) Photo-alignment film

[0258] As a photo-alignment material for an alignment film formed by light irradiation, there are records in a plurality of documents, etc. In the present invention, as preferred examples, for example, Japanese Patent Publication No. 2006-285197, Japanese Patent Publication No. 2007-76839, Japanese Patent Publication No. 2007-138138, Japanese Patent Publication No. 2007-094071, Japanese Patent Publication No. 2007-121721, Japanese Patent Publication No. 2007-140465, Japanese Patent Publication No. 2007-156439, Japanese Patent Publication No. 2007-133184, Japanese Patent Publication No. 2009-109831, Japanese Patent No. 3883848, Japanese Patent No. 4151746 can be cited. The present invention further comprises azo compounds, aromatic ester compounds described in Japanese Patent Application Laid-Open No. 2002-229039, maleimide and / or alkenyl-substituted nadic imide compounds having a photo-alignment unit described in Japanese Patent Application Laid-Open No. 2002-265541 and Japanese Patent Application Laid-Open No. 2002-317013, photo-crosslinkable silane derivatives described in Japanese Patent No. 4205195 and Japanese Patent No. 4205198, photo-crosslinkable polyimides, polyamides or esters described in Japanese Patent Publication No. 2003-520878, Japanese Patent Publication No. 2004-529220 or Japanese Patent No. 4162850. More preferably, the present invention further comprises azo compounds, photo-crosslinkable polyimides, polyamides or esters.

[0259] Among these, it is preferable to use, as the photo-alignment compound, a photosensitive compound having a photoreactive group that undergoes at least one of dimerization and isomerization by the action of light.

[0260] In addition, as the photoreactive group, for example, there can be mentioned a group having a cinnamic acid (cinnamoyl) structure (skeleton), a group having a coumarin structure (skeleton), a group having a chalcone structure (skeleton), a group having a benzophenone structure (skeleton), and a group having an anthracene structure (skeleton). Among these groups, a group having a cinnamoyl structure and a group having a coumarin structure are preferred, and a group having a cinnamoyl structure is more preferred.

[0261] Furthermore, the photosensitive compound having the above-mentioned photo-alignment group may further have a crosslinking group.

[0262] The crosslinkable group is preferably a thermal crosslinkable group that undergoes a curing reaction by heat or a photo crosslinkable group that undergoes a curing reaction by light, and may include both a thermal crosslinkable group and a photo crosslinkable group.

[0263] As the crosslinkable group, for example, at least one selected from the group consisting of an epoxy group, an oxetane group, a group represented by -NH-CH2-OR (R represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms), a group having an ethylenically unsaturated double bond, and a blocked isocyanate group can be cited. Among them, an epoxy group, an oxetane group, or a group having an ethylenically unsaturated double bond is preferred.

[0264] In addition, a three-membered ring cyclic ether group is also called an epoxy group, and a four-membered ring cyclic ether group is also called an oxetanyl group.

[0265] Specific examples of the group having an ethylenically unsaturated double bond include a vinyl group, an allyl group, a styryl group, an acryloyl group, and a methacryloyl group, and an acryloyl group or a methacryloyl group is preferred.

[0266] The photo-alignment film formed of the above-mentioned material is irradiated with linearly polarized light or non-polarized light to produce the photo-alignment film.

[0267] In this specification, "linearly polarized light irradiation" and "non-polarized light irradiation" refer to operations for causing a photo-alignment material to produce a photoreaction. The wavelength of the light used varies depending on the photo-alignment material used, and is not particularly limited as long as it is a wavelength required for the photoreaction. The peak wavelength of the light used in the photo-irradiation is preferably 200nm to 700nm, and more preferably ultraviolet light with a peak wavelength of 400nm or less.

[0268] The light source used in the light irradiation can include commonly used light sources, such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury-xenon lamps and carbon arc lamps, various lasers [for example, semiconductor lasers, helium-neon lasers, argon ion lasers, helium-cadmium lasers and YAG (yttrium aluminum garnet) lasers], light emitting diodes, and cathode ray tubes.

[0269] As a method of obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine-based polarizing plate, a dichroic polarizing plate, and a wire grid polarizing plate), a method using a prism element (e.g., a Glan-Thomson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a laser light source having polarized light can be adopted. In addition, a filter or a wavelength conversion element can be used to selectively irradiate only light of a desired wavelength.

[0270] When the irradiated light is linearly polarized light, the method of irradiating the light vertically or obliquely to the surface of the alignment film from the upper surface or the back surface of the alignment film is adopted. The incident angle of the light varies depending on the photo-alignment material, but is preferably 0 to 90° (vertical), preferably 40 to 90°.

[0271] In the case of non-polarized light, the non-polarized light is irradiated obliquely toward the alignment film, and the incident angle is preferably 10 to 80°, more preferably 20 to 60°, and further preferably 30 to 50°.

[0272] The irradiation time is preferably 1 minute to 60 minutes, more preferably 1 minute to 10 minutes.

[0273] When patterning is required, a method of irradiating light using a photomask a number of times required for patterning or a method of writing a pattern by laser scanning can be adopted.

[0274] [Orientation process]

[0275] The orientation step is a step of orienting the dichroic substance contained in the coating film. In this way, the light absorption anisotropic film of the present invention can be obtained. It is considered that in the orientation step, the dichroic substance is oriented along the liquid crystal compound oriented by the orientation film.

[0276] The orientation process may include a drying process. By drying, components such as the solvent can be removed from the coating film. The drying process may be performed by leaving the coating film at room temperature for a predetermined time (e.g., natural drying), or by heating and / or blowing air.

[0277] Here, the dichroic substance contained in the light absorbing anisotropic film-forming composition may be oriented by the above-mentioned coating film forming step or drying treatment. For example, in a mode in which the light absorbing anisotropic film-forming composition is prepared as a coating liquid containing a solvent, the solvent may be removed from the coating film by drying the coating film, and the dichroic substance contained in the coating film may be oriented, thereby obtaining the light absorbing anisotropic film of the present invention.

[0278] The orientation step preferably includes a heat treatment. This further orients the dichroic substance contained in the coating film, and the orientation degree of the obtained light absorption anisotropic film becomes higher.

[0279] From the viewpoint of production suitability, the heat treatment is preferably performed at 10 to 250° C., more preferably 25 to 190° C. The heating time is preferably 1 to 300 seconds, more preferably 1 to 60 seconds.

[0280] The heat treatment is preferably carried out in multiple stages with different heating temperatures. It is more preferable that after carrying out the first stage of heat treatment (e.g., 140°C, 10 seconds), after cooling to about room temperature (20-25°C), the second stage and subsequent heat treatments (e.g., 50-100°C, 15 seconds) are carried out at a temperature lower than that of the first stage of heat treatment (e.g., a temperature lower than 40-90°C).

[0281] It is presumed that the dichroic substance is brought into a nematic orientation state (an unintentionally existing arrangement structure is melted) by the first stage heat treatment, and then a desired arrangement structure of the dichroic substance is formed by the second stage heat treatment.

[0282] The orientation process may include a cooling process performed after the heating process. The cooling process is a process of cooling the heated coating film to about room temperature (20 to 25° C.). As a result, the orientation of the dichroic substance contained in the coating film is further fixed, and the orientation degree of the obtained light absorption anisotropic film becomes higher. The cooling method is not particularly limited and can be performed by a known method.

[0283] Through the above steps, the light absorption anisotropic film of the present invention can be obtained.

[0284] [Other processes]

[0285] The production method of the present invention may include a step of curing the light absorption anisotropic film after the alignment step (hereinafter also referred to as a "curing step").

[0286] The curing step is performed, for example, by heating and / or light irradiation (exposure). Among them, the curing step is preferably performed by light irradiation.

[0287] The light source used for curing can use various light sources such as infrared rays, visible light or ultraviolet rays, but ultraviolet rays are preferred. In addition, ultraviolet rays may be irradiated while heating during curing, or ultraviolet rays may be irradiated through a filter that transmits only a specific wavelength.

[0288] Furthermore, the exposure may be performed in a nitrogen atmosphere. When the light absorption anisotropic film is cured by radical polymerization, the inhibition of polymerization by oxygen can be reduced, so the exposure is preferably performed in a nitrogen atmosphere.

[0289] [Preferred Mode 1]

[0290] As a preferred embodiment of the production method of the present invention, there is mentioned an embodiment (preferred embodiment 1) in which the orientation step includes a step of exposing the coating film formed in the coating film forming step in the atmosphere (under atmospheric atmosphere) (hereinafter also referred to as "atmospheric exposure step").

[0291] When the coating film is exposed in the atmosphere, the free radicals in the area on the coating surface side (area A) are deactivated and polymerization is difficult to proceed, whereas polymerization (semi-curing) proceeds in the area on the alignment film side (area B). As a result, it is believed that the viscosity of area B increases, and the formation speed of the arrangement structure of the dichroic substance in area B decreases, thereby obtaining a light absorption anisotropic film with a small size (Llow) of the arrangement structure of area B. In addition, the value of Llow can be further adjusted according to the exposure conditions (illuminance, exposure time, etc.).

[0292] From the viewpoint of achieving more excellent effects of the present invention, the atmospheric exposure step is preferably performed after the first stage heat treatment, after cooling to about room temperature, and before the second stage heat treatment.

[0293] In the atmospheric exposure step, the illuminance is preferably 1 to 300 mW / cm 2 , more preferably 10 to 250 mW / cm 2 , more preferably 20 to 200 mW / cm 2 .

[0294] In the atmospheric exposure step, the irradiation time is preferably 0.05 to 10 seconds, more preferably 0.07 to 5 seconds, and even more preferably 0.1 to 2 seconds because the effects of the present invention and the like are more excellent.

[0295] [Preferred Mode 2]

[0296] Furthermore, as another preferred embodiment of the manufacturing method of the present invention, there can be cited a method in which the orientation step includes a step of exposing the coating film formed in the coating film forming step to ultraviolet rays that do not include light of 330 hm or more (hereinafter also referred to as "short-wavelength UV") (hereinafter also referred to as "short-wavelength UV exposure step") (preferred embodiment 2).

[0297] When the coating film is exposed to short-wavelength UV, polymerization (semi-curing) is performed in the area on the coating surface side (area A), while short-wavelength UV is difficult to transmit in the area on the alignment film side (area B), so polymerization is difficult to perform. As a result, it is believed that the viscosity of area A increases, and the formation speed of the arrangement structure of the dichroic substance in area A decreases, so that a light absorption anisotropic film with a small size (Ltop) of the arrangement structure of area A can be obtained. In addition, the value of Ltop can be further adjusted according to the exposure conditions (illuminance, exposure time, etc.).

[0298] As a method of generating short-wavelength UV, a method of performing UV exposure via a short-pass filter and the like are mentioned, for example.

[0299] From the viewpoint of achieving more excellent effects of the present invention, the short-wavelength UV exposure step is preferably performed after the first-stage heat treatment described above, after cooling to about room temperature, and before the second-stage heat treatment.

[0300] In the short-wavelength UV exposure step, the illuminance is preferably 1 to 500 mW / cm 2 , more preferably 10 to 400 mW / cm 2 , more preferably 20 to 300 mW / cm 2 .

[0301] In the atmospheric exposure step, the irradiation time is preferably 0.05 to 10 seconds, more preferably 0.07 to 5 seconds, and even more preferably 0.1 to 2 seconds because the effects of the present invention and the like are more excellent.

[0302] [3] Laminated body

[0303] The laminated body of the present invention is a laminated body having the above-mentioned light absorption anisotropic film of the present invention.

[0304] The laminate of the present invention may have a film (layer) other than the film of the present invention. Examples of such a film (layer) include a protective layer, an oriented film, a substrate, and an optically anisotropic film.

[0305] When the laminate of the present invention is applied to an image display device, it is preferred that the protective layer side is arranged on the visual recognition side (the incident side of light). By arranging the surface with low polarization degree (surface with low refractive index) on the protective layer side, the refractive index difference between the light absorption anisotropic film and the protective layer becomes small, thereby further suppressing internal reflection.

[0306] [Light absorption anisotropic film]

[0307] The light absorption anisotropic film of the present invention included in the laminate of the present invention is as described above, and therefore the description thereof will be omitted.

[0308] [Protective layer]

[0309] The protective layer is not particularly limited, and examples thereof include an oxygen barrier layer and a UV (ultraviolet) absorption layer. An oxygen barrier layer is preferred because the effects of the present invention are more excellent.

[0310] 〔Oxygen barrier layer〕

[0311] The oxygen barrier layer is an oxygen barrier film having an oxygen barrier function. In this specification, the oxygen barrier function is not limited to a state of being completely impermeable to oxygen, but also includes a state where a small amount of oxygen passes according to target performance.

[0312] Specific examples of the oxygen barrier layer include layers containing organic compounds such as polyvinyl alcohol, modified polyvinyl alcohol, polyethylene-vinyl alcohol, polyvinyl ether, polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, cellulose ether, polyamide, polyimide, styrene / maleic acid copolymer, gelatin, vinylidene chloride and cellulose nanofibers. Polyacrylic acid, polyvinyl alcohol or modified polyvinyl alcohol is preferred because the effects of the present invention are more excellent.

[0313] The oxygen barrier layer contains the above-mentioned organic compound and may further contain a light resistance improver from the viewpoint of further improving light resistance. When the oxygen barrier layer contains a light resistance improver, the content of the light resistance improver is preferably 0.1 to 5.0% by mass, more preferably 0.3 to 3.0% by mass, relative to the total mass of the oxygen barrier layer.

[0314] The thickness of the oxygen barrier layer is preferably 0.1 to 10 μm, more preferably 0.5 to 5.5 μm, because the effects of the present invention and the like are more excellent.

[0315] From the viewpoint of obtaining more excellent effects of the present invention, the refractive index of the protective layer at a wavelength of 550 nm is preferably 1.40 to 1.60, and more preferably 1.45 to 1.55.

[0316] Here, the refractive index of the protective layer at a wavelength of 550 nm can be measured by the same method as the average refractive index of the above-mentioned light absorption anisotropic film.

[0317] [Oriented film]

[0318] The alignment film included in the laminate of the present invention is the same as the alignment film used in the above-mentioned method for producing the light absorption anisotropic film, and therefore the description thereof is omitted.

[0319] [Base material]

[0320] The laminate of the present invention may have a substrate on the side of the alignment film opposite to the light absorption anisotropic film.

[0321] The substrate can be selected according to the application of the light absorption anisotropic film, and examples thereof include glass and polymer films.

[0322] When a polymer film is used as a substrate, an optically isotropic polymer film is preferably used. The specific examples and preferred embodiments of the polymer can be described in paragraph

[0013] of Japanese Patent Application Laid-Open No. 2002-22942. Furthermore, even if a polymer that is known to easily show birefringence, such as polycarbonate or polysulfone, is used, a polymer described in International Publication No. 2000 / 26705 that reduces the showability by modifying the molecule can be used.

[0323] The average visible light transmittance of the substrate is preferably 80% or more.

[0324] [Optically anisotropic film]

[0325] The laminated body of the present invention preferably has a light absorption anisotropic film (optically anisotropic layer).

[0326] Here, the optically anisotropic film refers to any film that generates a phase difference, and examples thereof include a stretched polymer film and a phase difference film in which an optically anisotropic layer having an aligned liquid crystal compound is provided on a support.

[0327] Here, the alignment direction of the liquid crystal compound contained in the optically anisotropic layer is not particularly limited, and examples thereof include horizontal, vertical, and twisted alignment with respect to the film surface.

[0328] Furthermore, specific functions of the optically anisotropic film include, for example, a λ / 4 plate and a λ / 2 plate.

[0329] Furthermore, the optically anisotropic layer may be composed of a plurality of layers. For an optically anisotropic layer composed of a plurality of optically anisotropic layers, for example, the description in paragraphs

[0008] to

[0053] of Japanese Patent Application Laid-Open No. 2014-209219 can be referred to.

[0330] Furthermore, the optically anisotropic film and the light absorption anisotropic film may be provided in contact with each other, or another layer may be provided therebetween. Examples of such a layer include the alignment film and an adhesive layer or bonding layer for ensuring adhesion.

[0331] The laminate of the present invention preferably uses a λ / 4 plate as the optically anisotropic film, and preferably has the λ / 4 plate on the side of the alignment film opposite to the light absorption anisotropic film.

[0332] Here, the “λ / 4 plate” refers to a plate having a λ / 4 function, and specifically, refers to a plate having a function of converting linearly polarized light of a certain wavelength into circularly polarized light (or converting circularly polarized light into linearly polarized light).

[0333] For example, as a mode in which the λ / 4 plate has a single-layer structure, specifically, a phase difference film in which a stretched polymer film or an optically anisotropic layer having a λ / 4 function is provided on a support, etc., and as a mode in which the λ / 4 plate has a multi-layer structure, specifically, a wide-band λ / 4 plate formed by stacking a λ / 4 plate and a λ / 2 plate can be mentioned.

[0334] The λ / 4 plate can be a plate having a wavelength dispersion property of anti-dispersion of the phase difference Re using an anti-dispersion liquid crystal compound. Here, the anti-dispersion wavelength dispersion property means that Re(λ) and Rth(λ) become larger as the wavelength λ increases, and at this time, the phase difference Re(λ) satisfies the following formula (Re-1) and formula (Re-2).

[0335] Formula (Re-1): Re(450) / Re(550)<1.0

[0336] Formula (Re-2): Re(650) / Re(550)>1.0

[0337] Colored If the wavelength dispersion of the phase difference Re has a wavelength dispersion of reverse dispersion, the reflection of external light can be reduced in all wavelength regions of visible light, and the coloring of reflected light can be suppressed, which is preferable.

[0338] [4] Image display device

[0339] The image display device of the present invention is an image display device including the above-mentioned light absorption anisotropic film (polarizer) of the present invention.

[0340] The display element used in the image display device of the present invention is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescent (organic EL) display panel, and a plasma display panel.

[0341] Among these, a liquid crystal cell or an organic EL display panel is preferred, and an organic EL display panel is more preferred. That is, as the image display device of the present invention, a liquid crystal display device using a liquid crystal cell as a display element, an organic EL display device using an organic EL display panel as a display element is preferred, and an organic EL display device is more preferred.

[0342] [Liquid crystal display device]

[0343] A liquid crystal display device as an example of the display device of the present invention is a liquid crystal display device including the above-mentioned laminated body of the present invention (but not including the λ / 4 plate) and a liquid crystal cell.

[0344] In the present invention, in the stacked bodies provided on both sides of the liquid crystal cell, the stacked bodies of the present invention are preferably used as polarizing elements on the front side (visual recognition side), and more preferably used as polarizing elements on the front and back sides.

[0345] Hereinafter, the liquid crystal cell constituting the liquid crystal display device will be described in detail.

[0346] 〔Liquid crystal unit〕

[0347] The liquid crystal cell used in the liquid crystal display device is preferably a VA (Vertical Alignment) mode, an OCB (Optically Compensated Bend) mode, an IPS (In-Plane-Switching) mode, or a TN (Twisted Nematic) mode, but is not limited thereto.

[0348] In a TN mode liquid crystal cell, rod-shaped liquid crystal molecules (rod-shaped liquid crystal compounds) are substantially horizontally aligned when no voltage is applied, and further twisted at 60 to 120 degrees. TN mode liquid crystal cells are most commonly used as color TFT liquid crystal display devices and are described in many documents.

[0349] In a VA-mode liquid crystal cell, rod-shaped liquid crystal molecules are substantially vertically aligned when no voltage is applied. VA mode liquid crystal cells include (1) a narrowly defined VA mode liquid crystal cell in which rod-shaped liquid crystal molecules are substantially vertically aligned when no voltage is applied and substantially horizontally aligned when a voltage is applied (described in Japanese Patent Application Laid-Open No. 2-176625), (2) a VA mode liquid crystal cell having multiple domains (MVA mode (Multi-domain Vertical Alignment)) in order to widen the viewing angle (described in SID97, Digest of tech. Papers 28 (1997) 845), (3) a liquid crystal cell in which rod-shaped liquid crystal molecules are substantially vertically aligned when no voltage is applied and have a twisted multi-domain alignment (n-ASM (Axially symmetric aligned microcell) mode) when a voltage is applied (described in Proceedings of the Japan Liquid Crystal Symposium 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (published in LCD (liquid crystal display) International 98). Furthermore, it may be any of PVA (Patterned Vertical Alignment), optical alignment (Optical Alignment), and PSA (Polymer-Sustained Alignment). Details of these modes are described in Japanese Unexamined Patent Publication No. 2006-215326 and Japanese Translation of National Publication No. 2008-538819.

[0350] In the IPS mode liquid crystal unit, the rod-shaped liquid crystal molecules are substantially parallel to the substrate, and the liquid crystal molecules are made to respond in a plane by applying an electric field parallel to the substrate surface. In the IPS mode, a black display is obtained when no electric field is applied, and the absorption axes of the upper and lower polarizers are orthogonal. In Japanese Patent Publication No. 10-54982, Japanese Patent Publication No. 11-202323, Japanese Patent Publication No. 9-292522, Japanese Patent Publication No. 11-133408, Japanese Patent Publication No. 11-305217, Japanese Patent Publication No. 10-307291, etc., a method of using an optical compensation sheet to reduce light leakage during black display in an oblique direction and improve the viewing angle is disclosed.

[0351] [Organic EL display device]

[0352] As an example of the display device of the present invention, i.e., an organic EL display device, for example, a preferred embodiment includes the above-mentioned laminate of the present invention (preferably including a λ / 4 plate) and an organic EL display panel in order from the visual recognition side. In this case, the laminate preferably includes a protective layer, a light absorption anisotropic film, an alignment film, and a λ / 4 plate in order from the visual recognition side.

[0353] The organic EL display panel is a display panel composed of an organic EL element in which an organic light emitting layer (organic electroluminescent layer) is sandwiched between electrodes (cathode and anode). The structure of the organic EL display panel is not particularly limited, and a known structure can be adopted.

[0354] Example

[0355] Below, the present invention is further described in detail according to embodiment.As long as do not depart from the gist of the present invention, then can suitably change the material, usage amount, ratio, processing content and processing step etc. shown in the following embodiment.Therefore, the scope of the present invention should not be interpreted restrictively by the embodiment shown below.

[0356] [Example 1]

[0357] [Production of transparent support]

[0358] The following composition was charged into a mixing tank and stirred to prepare a cellulose acetate solution to be used as a core layer cellulose acylate solution.

[0359]

[0360]

[0361] Compound F

[0362] [Chemical formula 4]

[0363]

[0364] 10 parts by mass of the following matting agent solution was added to 90 parts by mass of the above core layer cellulose acylate solution to prepare a cellulose acetate solution to be used as an outer layer cellulose acylate solution.

[0365]

[0366] After filtering the core layer cellulose acylate solution and the outer layer cellulose acylate solution with filter paper having an average pore size of 34 μm and a sintered metal filter having an average pore size of 10 μm, the three layers of the core layer cellulose acylate solution and the outer layer cellulose acylate solutions on both sides thereof are simultaneously cast from a casting port onto a drum (endless belt casting machine) at 20°C.

[0367] Next, the film on the roll was peeled off when the solvent content in the film was about 20% by mass, and both ends of the film in the width direction were fixed with tenter clips, and the film was dried while being stretched in the transverse direction at a stretching ratio of 1.1 times.

[0368] Thereafter, the obtained film was conveyed between rollers of a heat treatment device and further dried to prepare a transparent support having a thickness of 40 μm. This was referred to as a cellulose acylate film A1.

[0369] [Formation of Photo-Alignment Film B1]

[0370] The photo-alignment film-forming composition described later was continuously coated on the cellulose acylate film A1 by a wire bar. The support with the coating film was dried with 140° C. hot air for 120 seconds, and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 , using an ultra-high pressure mercury lamp), thereby forming a photo-alignment film B1, thereby obtaining a TAC (triacetyl cellulose) film with a photo-alignment film. The film thickness of the photo-alignment film B1 is 0.25 μm.

[0371]

[0372] Polymer PA-1 (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)

[0373] [Chemical formula 5]

[0374]

[0375] Acid Generator PAG-1

[0376] [Chemical formula 6]

[0377]

[0378] Stabilizer DIPEA

[0379] [Chemical formula 7]

[0380]

[0381] [Preparation of light absorption anisotropic film C1]

[0382] <Coating film forming step>

[0383] A light absorption anisotropic film-forming composition having the following composition was continuously applied on the obtained photo-alignment film B1 using a wire bar to form a coating film.

[0384] <Orientation Process>

[0385] Next, the coating film was heated at 140° C. for 15 seconds, and then cooled to room temperature (23° C.).

[0386] Next, the coating film was heated at 75° C. for 60 seconds and cooled to room temperature again.

[0387] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2 The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.

[0388] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%. The absorption axis of the light absorption anisotropic film C1 was orthogonal to the width direction of the cellulose acylate film A1.

[0389] In addition, in the light absorption anisotropic film C1, the surfactant tends to exist near the surface on the coating surface side, and accordingly, polyethylene oxide (PEO) having a high affinity for the above-mentioned surfactant (low LogP value (octanol / water partition coefficient)) also tends to exist in area A on the coating surface side.

[0390]

[0391]

[0392] Dichroic substance Dye-C 1

[0393] [Chemical formula 8]

[0394]

[0395] Dichroic Material Dye-M1

[0396] [Chemical formula 9]

[0397]

[0398] Dichroic Material Dye-Y1

[0399] [Chemical formula 10]

[0400]

[0401] Liquid crystal compound (L-1) (wherein the numerical values ​​("59", "15", "26") described in each repeating unit represent the content (mass %) of each repeating unit relative to all repeating units.)

[0402] [Chemical formula 11]

[0403]

[0404] Rod-like liquid crystal compound (L-2) (wherein the numerical value described in each compound represents the content (mass %) of each compound relative to all compounds.)

[0405] [Chemical formula 12]

[0406]

[0407] Surfactant (F-1) (wherein the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)

[0408] [Chemical formula 13]

[0409]

[0410] [Formation of oxygen barrier layer D1]

[0411] A coating liquid D1 having the following composition was continuously coated on the light absorbing anisotropic film C1 by a wire bar. Thereafter, by drying with warm air at 80° C. for 5 minutes, a laminated body having an oxygen barrier layer D1 of 1.0 μm thick made of polyvinyl alcohol (PVA) was obtained, that is, a laminated body CP1 having a cellulose acylate film A1 (transparent support), a photo-alignment film B1, a light absorbing anisotropic film C1, and an oxygen barrier layer D1 adjacent to each other in this order was obtained.

[0412]

[0413] Modified polyvinyl alcohol (wherein the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)

[0414] [Chemical formula 14]

[0415]

[0416] [Production of TAC film with positive A plate]

[0417] The coating liquid E1 for forming a photo-alignment film having the following composition was continuously coated on the cellulose acylate film A1 using a wire bar. The support body with the coating film was dried with warm air at 140° C. for 120 seconds, and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 , using an ultra-high pressure mercury lamp), thereby forming a photo-alignment film E1 with a thickness of 0.2 μm, and obtaining a TAC film with a photo-alignment film.

[0418]

[0419] Acid Generator CPI-110TF

[0420] [Chemical formula 15]

[0421]

[0422] Polymer PA-2 (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)

[0423] [Chemical formula 16]

[0424]

[0425] The composition F1 with the following composition was applied onto the photo-alignment film E1 using a bar coater. The coating formed on the photo-alignment film E1 was heated to 120° C. using hot air, then cooled to 60° C., and then irradiated with 100 mJ / cm 2 at a wavelength of 365 nm using a high-pressure mercury lamp in a nitrogen atmosphere. 2 The coating film was irradiated with ultraviolet rays and then heated to 120°C while 500 mJ / cm 2 The coating film was irradiated with ultraviolet rays, thereby fixing the orientation of the liquid crystal compound, thereby producing a TAC film having a positive A plate F1.

[0426] The thickness of the positive A plate F1 is 2.5 μm, and Re(550) is 144 nm. In addition, the positive A plate satisfies the relationship Re(450)≤Re(550)≤Re(650). Re(450) / Re(550) is 0.82.

[0427]

[0428] Polymerizable liquid crystal compound LA-1 (tBu represents tert-butyl group)

[0429] [Chemical formula 17]

[0430]

[0431] Polymerizable liquid crystal compound LA-2

[0432] [Chemical formula 18]

[0433]

[0434] Polymerizable liquid crystal compound LA-3

[0435] [Chemical formula 19]

[0436]

[0437] Polymerizable liquid crystal compound LA-4 (Me represents methyl group)

[0438] [Chemical formula 20]

[0439]

[0440] Polymerization initiator PI-1

[0441] [Chemical formula 21]

[0442]

[0443] Leveling agent T-1 (wherein the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.

[0444] [Chemical formula 22]

[0445]

[0446] [Manufacturing of TAC film having positive C plate H1]

[0447] As the pseudo support, the above-mentioned cellulose acylate film A1 was used.

[0448] The cellulose acylate film A1 was passed through a dielectric heating roller at a temperature of 60° C. to raise the surface temperature of the film to 40° C., and then coated on one side of the film with a coating amount of 14 ml / m 2 An alkaline solution having the composition shown below was applied, heated to 110° C., and conveyed under a steam-type far-infrared heater manufactured by NORITAKE CO., LIMITED for 10 seconds.

[0449] Next, pure water (3 ml / m2) was applied to the membrane using a bar coater. 2Next, after water washing with a jet coater and dehydration with an air knife were repeated three times, the film was conveyed in a drying zone at 70° C. for 10 seconds to be dried, thereby producing an alkali saponified cellulose acylate film A1.

[0450]

[0451] The photo-alignment film-forming coating liquid G1 having the following composition was continuously coated on the alkali-saponified cellulose acylate film A1 using a #8 wire bar. The obtained film was dried with 60°C hot air for 60 seconds and further with 100°C hot air for 120 seconds to form a photo-alignment film G1.

[0452]

[0453]

[0454] A coating liquid H1 for forming a positive C plate having the following composition was applied onto the photo-alignment film G1, and the obtained coating film was aged at 60° C. for 60 seconds and then heated at 70 mW / cm in air. 2 An air-cooled metal halide lamp (manufactured by Eyegraphics Co., Ltd.) was used to irradiate 1000 mJ / cm 2 The orientation state was fixed by ultraviolet rays, thereby vertically aligning the liquid crystal compound, thereby producing a TAC film having a positive C plate H1 with a thickness of 0.5 μm.

[0455] The Rth(550) of the obtained positive C plate was -60 nm.

[0456]

[0457] Liquid crystal compound LC-1

[0458] [Chemical formula 23]

[0459]

[0460] Liquid crystal compound LC-2

[0461] [Chemical formula 24]

[0462]

[0463] Vertically aligned liquid crystal compound S01

[0464] [Chemical formula 25]

[0465]

[0466] Compound B03 (wherein the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)

[0467] [Chemical formula 26]

[0468]

[0469] [Preparation of Adhesives N1 and N2]

[0470] Next, an acrylic polymer was prepared according to the following steps.

[0471] In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer and a stirring device, 95 parts by mass of butyl acrylate and 5 parts by mass of acrylic acid were polymerized by a solution polymerization method to obtain an acrylic acid ester polymer (NA1) having an average molecular weight of 2,000,000 and a molecular weight distribution (Mw / Mn) of 3.0.

[0472] Next, an acrylic adhesive was prepared with the following composition using the obtained acrylic polymer (NA1). These compositions were applied to a separation membrane surface-treated with a silicone release agent using a die coater, dried at 90° C. for 1 minute, and irradiated with ultraviolet light (UV) under the following conditions, thereby obtaining the following acrylic adhesives N1 and N2 (adhesive layer). The composition and film thickness of the acrylic adhesive are shown below.

[0473] <UV irradiation conditions>

[0474] FUSION Co., Ltd.'s electrodeless lamp H bulb

[0475] Illuminance 600mW / cm 2 , light intensity 150mJ / cm 2

[0476] The UV illuminance and light quantity were measured using “UVPF-36” manufactured by EYE GRAPHICS COMPANY.

[0477]

[0478] (A) Multifunctional acrylic monomer: tri(acryloyloxyethyl)isocyanurate, molecular weight = 423, trifunctional type (manufactured by TOAGOSEI CO., LTD., product name "ARONIX M-315")

[0479] (B) Photopolymerization initiator: a mixture of benzophenone and 1-hydroxycyclohexyl phenyl ketone in a mass ratio of 1:1, "Irgacure 500" manufactured by Ciba Specialty Chemicals Co., Ltd.

[0480] (C) Isocyanate crosslinking agent: trimethylolpropane-modified toluene diisocyanate ("CORONATE L" manufactured by Nippon Polyurethane Industry Co., Ltd.)

[0481] (D) Silane coupling agent: 3-glycidyloxypropyltrimethoxysilane ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.)

[0482] [Production of UV Adhesive]

[0483] A UV adhesive composition having the following composition was prepared.

[0484]

[0485]

[0486] CPI-100P

[0487] [Chemical formula 27]

[0488]

[0489] [Preparation of laminated body CPAC1]

[0490] Using the above UV adhesive composition, at 600mJ / cm 2 The phase difference side of the TAC film having the positive A plate F1 and the phase difference side of the TAC film having the positive C plate H1 are bonded under UV irradiation. The thickness of the UV adhesive layer is 3 μm. In addition, the surfaces bonded by the UV adhesive are respectively subjected to corona treatment. Next, the photo-alignment film E1 and the cellulose acylate film A1 on the side of the positive A plate F1 are removed, and the phase difference plate AC 1 is used. In addition, the layer structure of the phase difference plate AC1 is the positive A plate F1, the UV adhesive layer, the positive C plate H1, the photo-alignment film G1 and the cellulose acylate film A1.

[0491] Using the above-mentioned adhesive N1, the oxygen barrier layer D1 side of the above-mentioned laminate CP1 is bonded to the support side of the low-reflection surface film CV-LC5 (manufactured by Fujifilm Corporation). Next, only the cellulose acylate film A1 contained in the above-mentioned laminate CP1 is removed, and the removed surface and the positive A plate F1 side of the above-mentioned phase difference plate AC1 are bonded using the above-mentioned adhesive N1. Next, the optical orientation film G1 and the cellulose acylate film A1 on the positive C plate H1 side contained in the above-mentioned phase difference plate AC1 are removed to produce the laminate CPAC1. At this time, the angle formed by the absorption axis of the light absorption anisotropic film C1 contained in the above-mentioned laminate CPAC1 and the slow axis of the positive A plate F1 is bonded to 45°. In addition, the layer structure of the stacked body CPAC1 is a low-reflection surface film CV-LC5, an adhesive layer N1, an oxygen barrier layer D1, a light absorption anisotropic film C1, a light orientation film B1, an adhesive layer N1, a positive A plate F1, a UV adhesive layer and a positive C plate H1.

[0492] [Manufacturing of organic EL display device (display device 1)]

[0493] The GALAXY S5 manufactured by SAMSUNG equipped with an organic EL panel (organic EL display element) was disassembled, and the touch panel with a circular polarizer was peeled off from the organic EL display device, and then the circular polarizer was peeled off from the touch panel, so that the organic EL display element, the touch panel and the circular polarizer were separated. Then, the separated touch panel was again bonded to the organic EL display element, and then the positive C plate H1 side of the laminated body CPAC1 prepared above was bonded to the touch panel to prevent air from entering, thereby manufacturing an organic EL display device (display device 1).

[0494] [Manufacturing of organic EL display device (display device 2)]

[0495] After the light absorption anisotropic film C1 was prepared, the cellulose acylate film A was attached to the surface of the light absorption anisotropic film C1 on the side opposite to the photo alignment film B1, and then the cellulose acylate film A on the photo alignment film B1 side was removed, and the oxygen barrier layer D1 was formed on the photo alignment film B1. In addition, the same steps as the above-mentioned laminated body CP1 were followed to obtain a laminated body CP2 having a cellulose acylate film A1 (transparent support), a light absorption anisotropic film C1, a photo alignment film B1, and an oxygen barrier layer D1 adjacent to each other in this order. In addition, an organic EL display device (display device 2) was produced in the same steps as the display device 1 except that the laminated body CP2 was used instead of the laminated body CP1.

[0496] [Example 2]

[0497] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film-forming composition having the following composition was used as the light absorption anisotropic film-forming composition.

[0498] In the light absorption anisotropic film C1 , since the ΔSP value (the difference in solubility parameter) of EPICLON N-695 with respect to the photo-alignment film B1 is small, the EPICLON N-695 is concentrated in the region B on the photo-alignment film B1 side.

[0499]

[0500]

[0501] EPICLON N-695 (cresol novolac type epoxy resin) manufactured by DIC Corporation (Mw=2,100)

[0502] [Example 3]

[0503] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film-forming composition having the following composition was used as the light absorption anisotropic film-forming composition.

[0504] In the light absorption anisotropic film C1, polyethylene oxide (PEO) is concentrated in region A on the coating surface side as in Example 1, and EPICLON N-695 is concentrated in region B on the photo-alignment film B1 side as in Example 2.

[0505]

[0506] [Example 4]

[0507] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film C1 was produced as follows.

[0508] (Fabrication of light absorption anisotropic film C1)

[0509] <Coating film forming step>

[0510] The optically anisotropic film-forming composition having the following composition was continuously applied on the photo-alignment film B1 using a wire bar to form a coating film.

[0511] <Orientation Process>

[0512] Next, the coating film was heated at 140° C. for 15 seconds, and then cooled to room temperature (23° C.).

[0513] Next, use an LED (light emitting diode) lamp (central wavelength 365nm) at an illumination of 10mW / cm 2 Under the irradiation conditions, the exposure was carried out for 0.5 seconds in the atmospheric atmosphere.

[0514] Next, the coating film was heated at 75° C. for 60 seconds and cooled to room temperature again.

[0515] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2 The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.

[0516] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%.

[0517] The absorption axis of the light absorption anisotropic film C1 is orthogonal to the width direction of the cellulose acylate film A1.

[0518]

[0519]

[0520] [Example 5]

[0521] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film C1 was produced as follows.

[0522] [Preparation of light absorption anisotropic film C1]

[0523] <Coating film forming step>

[0524] The optically anisotropic film-forming composition having the same composition as that in Example 4 was continuously applied to the photo-alignment film B1 using a wire bar to form a coating film.

[0525] <Orientation Process>

[0526] Next, the coating film was heated at 140° C. for 15 seconds, and then cooled to room temperature (23° C.).

[0527] Next, use an LED (light emitting diode) lamp (central wavelength 365nm) at an illumination of 20mW / cm 2Under the irradiation conditions, the image was irradiated for 1 second in the atmospheric atmosphere.

[0528] Next, the coating film was heated at 75° C. for 60 seconds and cooled to room temperature again.

[0529] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2 The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.

[0530] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%.

[0531] The absorption axis of the light absorption anisotropic film C1 is orthogonal to the width direction of the cellulose acylate film A1.

[0532] [Example 6]

[0533] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film C1 was produced as follows.

[0534] [Preparation of light absorption anisotropic film C1]

[0535] <Coating film forming step>

[0536] The optically anisotropic film-forming composition having the same composition as that in Example 4 was continuously applied to the photo-alignment film B1 using a wire bar to form a coating film.

[0537] <Orientation Process>

[0538] Next, the coating film was heated at 140° C. for 15 seconds, and then cooled to room temperature (23° C.).

[0539] Next, a high-pressure mercury lamp equipped with a 310 nm short-pass filter was used at an illumination of 50 mW / cm 2 The irradiation was performed for 2 seconds under the irradiation conditions.

[0540] Next, the coating film was heated at 75° C. for 60 seconds and cooled to room temperature again.

[0541] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.

[0542] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%.

[0543] The absorption axis of the light absorption anisotropic film C1 is orthogonal to the width direction of the cellulose acylate film A1.

[0544] [Example 7]

[0545] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that a light absorption anisotropic film C1 was produced as follows.

[0546] [Preparation of light absorption anisotropic film C1]

[0547] <Coating film forming step>

[0548] The optically anisotropic film-forming composition having the same composition as that in Example 4 was continuously applied to the photo-alignment film B1 using a wire bar to form a coating film.

[0549] <Orientation Process>

[0550] Next, the coating film was heated at 140° C. for 15 seconds, and then cooled to room temperature (23° C.).

[0551] Next, a high-pressure mercury lamp equipped with a 310 nm short-pass filter was used at an illumination of 10 mW / cm 2 The irradiation was performed for 2 seconds under the irradiation conditions.

[0552] Next, the coating film was heated at 75° C. for 60 seconds and cooled to room temperature again.

[0553] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2 The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.

[0554] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%.

[0555] The absorption axis of the light absorption anisotropic film C1 is orthogonal to the width direction of the cellulose acylate film A1.

[0556] [Example 8]

[0557] In the preparation of the light absorption anisotropic film C1, organic EL display devices (display device 1, display device 2) were prepared in the same procedure as in Example 4 except that the light absorption anisotropic film-forming composition having the following composition was used.

[0558]

[0559] Dichroic substance Dye-C2

[0560] [Chemical formula 28]

[0561]

[0562] [Example 9]

[0563] In the preparation of the light absorption anisotropic film C1, organic EL display devices (display device 1, display device 2) were prepared in the same procedure as in Example 6 except that a light absorption anisotropic film-forming composition having the same composition as in Example 8 was used.

[0564] [Example 10]

[0565] In the preparation of the light absorption anisotropic film C1, organic EL display devices (display device 1, display device 2) were prepared in the same procedure as in Example 4 except that the light absorption anisotropic film-forming composition having the following composition was used.

[0566]

[0567] Dichroic substance Dey-Y2

[0568] [Chemical formula 29]

[0569]

[0570] [Example 11]

[0571] In the preparation of the light absorption anisotropic film C1, organic EL display devices (display device 1, display device 2) were prepared in the same procedure as in Example 6 except that a light absorption anisotropic film-forming composition having the same composition as in Example 10 was used.

[0572] [Example 12]

[0573] In the preparation of the light absorption anisotropic film C1, organic EL display devices (display device 1, display device 2) were prepared in the same procedure as in Example 6 except that the light absorption anisotropic film-forming composition having the following composition was used.

[0574]

[0575]

[0576] Liquid crystal compound (L-3)

[0577] [Chemical formula 30]

[0578]

[0579] Liquid crystal compound (L-4)

[0580] [Chemical formula 31]

[0581]

[0582] [Comparative Example 1]

[0583] Organic EL display devices (display device 1, display device 2) were produced in the same manner as in Example 1 except that the light absorption anisotropic film-forming composition of Example 4 was used as the light absorption anisotropic film-forming composition.

[0584] [Observation of the arrangement structure]

[0585] For each example of the light absorption anisotropic film C1, Ltop, Llow and Lmid were measured by the above method. As described above, the photo alignment film B1 side is region B (Llow), and the side opposite to the photo alignment film B1 is region A (Ltop). The results are shown in Table 1.

[0586] [evaluate]

[0587] The following evaluations were performed on the produced organic EL display device.

[0588] 〔Black contrast〕

[0589] The display screen of the produced organic EL display device (display device 1, display device 2) was set to black display, and the reflected light when the fluorescent light was reflected from the front was observed. In addition, the black contrast was evaluated according to the following criteria. The results are shown in Table 1. In actual use, at least one of the display device 1 and the display device 2 is preferably A or B, and more preferably A.

[0590] A: It is black and no color can be visually identified.

[0591] B: Red coloring is slightly visually recognized, but acceptable.

[0592] C: Red coloration is clearly visible and unacceptable.

[0593] Durability

[0594] The display device with the better black contrast among display devices 1 and 2 was subjected to 500 hours in an environment of 80°C and a relative humidity of less than 10%. Thereafter, the display screen of the organic EL display device was set to black display, and the reflected light when the fluorescent light was reflected from the front was observed. In addition, the durability was evaluated according to the following criteria. In actual use, A or B is preferred, and A is more preferred.

[0595] A: It is black and no color can be visually identified.

[0596] B: Coloring is slightly visible, but acceptable.

[0597] C: Coloration is clearly visible and unacceptable.

[0598]

[0599] As can be seen from Table 1, Examples 1 to 12 satisfying at least one of the formula (1-1) and the formula (1-2) all exhibited excellent black contrast.

[0600] Furthermore, from the comparison of Examples 1 to 12, Examples 1 to 4 and Examples 6 to 12 satisfying the formula (3-1) showed excellent durability.

[0601] Furthermore, as can be seen from the comparison of Examples 1 to 12, Examples 1 to 6 and Examples 8 to 12 in which at least one of Ltop and Llow is 30 nm or less show a more excellent black contrast.

[0602] On the other hand, in Comparative Example 1 which does not satisfy both the formula (1-1) and the formula (1-2), the black contrast is insufficient.

[0603] Explanation of symbols

[0604] a-one surface, b-the other surface, c-the center in the film thickness direction, A-region A, B-region B, C-region C, 100-light absorption anisotropic film.

Claims

1. A light absorption anisotropic film comprising a dichroic substance and a liquid crystal compound, wherein: At least a portion of the dichroic material forms an aligned structure, In a cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in a region A from one surface to 150 nm in the film thickness direction is set to Ltop, and the average value of the length of the major axis of the arrangement structure observed in a region B from the other surface to 150 nm in the film thickness direction is set to Llow, the light absorption anisotropic film satisfies at least one of the following formula (1-1) and the following formula (1-2), Ltop≤35nm(1-1), Llow≤35nm(1-2).

2. The light absorption anisotropic film according to claim 1, wherein: In a cross section observed by a scanning transmission electron microscope, when the average value of the length of the major axis of the arrangement structure observed in a region C of 150 nm in the central direction of the film thickness is set to Lmid, the light absorption anisotropic film satisfies at least one of the following formula (2-1) and the following formula (2-2), Ltop / Lmid<0.87(2-1), Llow / Lmid<0.87(2-2).

3. The light absorption anisotropic film according to claim 1, wherein: Satisfies the following formula (3-1), Lmid>40nm(3-1).

4. The light absorption anisotropic film according to claim 1, wherein: A substance that is preferentially present in at least one of the region A and the region B is contained.

5. The light absorption anisotropic film according to claim 4, wherein: The weight average molecular weight of the partial existence substance is 1,000 or more.

6. A manufacturing method, which is a manufacturing method of the light absorption anisotropic film according to any one of claims 1 to 5, comprising: a coating film forming step of forming a coating film by coating a light absorption anisotropic film-forming composition containing a dichroic substance and a liquid crystal compound on the alignment film; and The orientation step is to orient the dichroic material contained in the coating film to obtain a light absorption anisotropic film.

7. The manufacturing method according to claim 6, wherein: The alignment step includes exposing the coating film to air.

8. The manufacturing method according to claim 6, wherein: The alignment step includes exposing the coating film to ultraviolet light that does not include light of 330 nm or more. 9 . A laminate comprising the light absorption anisotropic film according to claim 1 , and a λ / 4 plate. 10 . An image display device comprising the light absorption anisotropic film according to claim 1 .

Citation Information

Patent Citations

  • Photosensitive compound containing trichloromethyl group, manufacture and photosensitive mixture

    JP1985105667A

  • Acylphosphine oxide compound*its manufacture and its use

    JP1988040799B2

  • Liquid crystal display device

    JP1990176625A

  • Bisacylphosphine oxide, manufacture and use

    JP1993029234B2

  • Phase difference plate and liquid crystal device provided with the same

    JP1997292522A